The An Analysis Of Policy Planning For The Construction Of A Thousand Smooth Roads In Seluma Regency In 2021 - Pauzi Asri; Antonio Imanda; Evi Lorita (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Abstrak